Genomic characterization of a multidrug-resistant Citrobacter portucalensis isolate co-harboring blaKPC–2 and blaNDM–1 on distinct plasmids - Huang, Junwei; Shen, Kai; Chen, Keqiang; Wu, Junliang; Zhu, Yijun; Shi, Jingchao (Frontiers in Microbiology, 2025)
BackgroundCitrobacter portucalensis is an emerging multidrug-resistant (MDR) pathogen within the Citrobacter genus. Although individual occurrences of blaKPC–2 or blaNDM–1 have been sporadically reported, the coexistence of both carbapenemase genes in a single strain remains extremely rare.MethodsWe performed whole-genome sequencing and conjugation assays on a bloodstream isolate of C. portucalensis (JH112) obtained from a critically ill patient. Plasmid structure, resistance determinants, and transferability were comprehensively analyzed using in vitro assays and bioinformatic pipelines.ResultsJH112 exhibited an extensively drug-resistant phenotype and carried two major carbapenemase genes, blaKPC–2 and blaNDM–1, located on distinct plasmids. The blaKPC–2 gene resided on an IncFII(Yp)-type plasmid (∼110 kb) with a complete conjugation module and was successfully transferred to a recipient strain. This plasmid also harbored an O-antigen biosynthesis gene cluster, potentially enhancing host adaptation. In contrast, the blaNDM–1 gene was located on a 340 kb IncHI2/HI2A-type megaplasmid with incomplete conjugation machinery and failed to transfer under standard conditions. Both plasmids showed unique structural arrangements compared to known references. The chromosome also carried blaCMY–49 and qnrB1, contributing to broad-spectrum resistance.ConclusionWe report a rare clinical C. portucalensis isolate co-harboring two carbapenemase genes on genetically distinct plasmids with divergent mobility. This highlights the species’ potential role as a resistance gene reservoir and the need for enhanced molecular surveillance in both clinical and environmental settings.